Interactive Robot for Automated Question and Answer System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims in developing an intelligent interactive robot with multi-functions which provides entertainment and companion. To obtain the information accurately, we have used speech recognition to perform the operations. For the Robot behavior, planning, interactions with the voice assistant and interactions with the user the various speech recognition results are applied. The robot has a simple design. In this study, we have used the microphone for speech recognition.  In addition, we have used room automation, notice display using voice message of the intelligent interaction between human and robots.